212. Outcomes of Weekly Fluconazole Antifungal Prophylaxis in Pancreas Transplant Recipients. (15th December 2022) - Williams, Samantha M; Vijayvargiya, Prakhar; Rizwan Sohail, M; Beam, Elena; Garrigos, Zerelda Esquer
Abstract: Background: Fungal infections following pancreas transplantation carry significant morbidity and mortality with an estimated incidence of 3 to 28%. The American Society of Transplantation (AST) suggests considering fluconazole prophylaxis in pancreas transplant recipients (PTR) at high-risk of invasive candidiasis (IC). However, optimal dosage and duration of prophylaxis is unclear. Weekly fluconazole for prevention of IC has been previously reported in liver and bone marrow transplant recipients. We analyzed outcomes of once weekly fluconazole prophylaxis in PTR. Methods: We retrospectively reviewed all pancreas transplants performed at our institution from January 2017 through September 2021. PTR at high-risk for IC were defined per AST criteria as those with enteric drainage, vascular thrombosis, and post-perfusion pancreatitis. Patients received once weekly oral fluconazole 200 mg for 12 weeks post-transplant for IC prophylaxis. We analyzed incidence of breakthrough IC within the first 6 months post-transplant. Results: We identified a total of 22 PTR, all of whom received simultaneous kidney transplantation from deceased donors. Of these, 12/22 (55%) were male and 11/22 (50%) were African American. Median age at the time of transplantation was 39 years (IQR 34-46). The most common indication for transplantation was type 1 diabetes mellitus (17/22, 21%) with associated nephropathy. No donor organ cultures were positive for fungi and all pancreas transplants were performed using enteric drainage. Notably, one patient developed pancreas allograft thrombosis while another developed pancreatitis. No patients required early discontinuation of fluconazole due to intolerance or side effects and none developed breakthrough IC within 6 months post-transplant (Table 1). Table 1. Conclusion: Weekly fluconazole prophylaxis has not been previously studied in PTR. In our cohort, this approach was well tolerated, with no cases of IC at 6 months post-transplantation in patients at high-risk. Randomized controlled clinical trials are needed to define the optimal strategy in this population. Disclosures: M. Rizwan Sohail, MD, Aziyo Biologics: Honoraria|Boston Scientific Corporation: Honoraria|Medtronic: Grant/Research Support|TRYX: Grant/Research Support.